2012
DOI: 10.1111/j.1582-4934.2011.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Cx31.1 acts as a tumour suppressor in non‐small cell lung cancer (NSCLC) cell lines through inhibition of cell proliferation and metastasis

Abstract: Reduced connexin expression and loss of gap junction function is a characteristic of many cancers, including lung cancer. However, there are little reports about the relation between Cx31.1 and lung cancer. This study was conducted to investigate the effect of Cx31.1 on non-small cell lung cancer (NSCLC). We found that the Cx31.1 was down-regulated in NSCLC cell lines, and the expression levels were reversely related with their metastatic potential. We ectopically expressed Cx31.1 in H1299 NSCLC cell line to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Cancer cells (including liver cancer, lung carcinoma and breast carcinoma) are generally linked to loss of connexin and/or GJIC (15,(31)(32)(33). Numerous studies have revealed the significant role of GJs in tumors, since recovered expression of connexin that forms GJs or recovered function of GJs could reduce the cell malignant phenotype (11,34,35).…”
Section: A B Discussionmentioning
confidence: 99%
“…Cancer cells (including liver cancer, lung carcinoma and breast carcinoma) are generally linked to loss of connexin and/or GJIC (15,(31)(32)(33). Numerous studies have revealed the significant role of GJs in tumors, since recovered expression of connexin that forms GJs or recovered function of GJs could reduce the cell malignant phenotype (11,34,35).…”
Section: A B Discussionmentioning
confidence: 99%
“…Moreover, a recent study found that Cx31.1 may act on migration and invasion of lung cancer cells. In such a study, the overexpression of Cx31.1 in the lung cancer cells (H1299 cells) eliminates their 3D migration and invasion by inducing mesenchymal–epithelial transition (MET) [61].…”
Section: Motilitymentioning
confidence: 99%
“…However, mutations in these genes account for only a minority of breast cancer and the exact molecular mechanisms underlying genetic susceptibility to this disease are still under intensive investigation. It is suggested that low-penetrance susceptibility genes combined with environmental factors may contribute to the development of cancer (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%